Y²-5Y+4=0 Y1=-(-5/2) - Square root of ((-5/2)²-4) Y1= 2.5 - Square root of 2.25 Y1 = 1 Y2=-(-5/2) + Square root of ((-5/2)²-4) Y2= 2.5 + Square root of 2.25 Y2 = 4 Y can be either 1 or 4
many solutions
8x2 + 16x + 8 = 0
x=-.25.
-y + y equals 0.
x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.
a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28
y= -2x
-1 plus 1 = 0 plus 1 =1
X = 1.8
2x(3x+6) = 0 x = 0 or x = -2
c= -2 2/7 OR -2.285714
p is obviously zero because any number x plus 0 equals itself.